Conservation payments, off-farm employment and household welfare for farmers participating in the "Grain for Green" program in China: Empirical evidence from the Loess Plateau. Issue 1 (30th October 2019) - Li, Li; Tsunekawa, Atsushi; MacLachlan, Ian; Li, Guicai; Koike, Atsushi; Guo, Yuanyuan
Abstract : Purpose: The purpose of this paper is to examine the factors (including conservation payments) that influence household decisions to participate in off-farm work and estimate the impact of participation on household welfare under the auspices of the Grain for Green (GfG) program. Design/methodology/approach: The authors used survey data from 225 farm households on the Loess Plateau and addressed the possible sample selection and endogeneity problems by employing a jointly estimated endogenous switching regression (ESR) model. Findings: The findings of this paper are as follows: off-farm participation is positively related to households' educational attainment and negatively related to their land resource endowment and the presence of children; participation in off-farm work exerts positive effects on household income and per capita household income, but negative effects on farm productivity; and conservation payments show no significant impact on off-farm participation, no significant impact on any of the three household welfare indicators for off-farm non-participant households, but a significantly negative impact for off-farm participant households. Originality/value: This paper makes two contributions. First, the authors address the selection bias and endogeneity problem of GfG participating households by employing the ESR method and explicitly estimating the treatment effects of off-farm participation on their household welfare. Neglecting these problems leads to biased estimates and misleading policy implications. Second, this analysis stresses the important role of government in reducing market or institutional failure and other barriers that impede farmers' efficient allocation choices instead of compensating households for conserving sloping land, shedding new light on the most effective policy options to achieve the program's goals.